A Literature Review of the Research on Markups of China’s Manufacturing Exports and Non-Export Firms - Wang, Yanfen (Journal of Accounting, Business and Finance Research, 2019)
According to the variable markup trade theory and the industrial organizational theory, generally higher markup means stronger market pricing power and higher productivity for a firm, while higher-productivity firms choose to export, which means the markup of export firms should be higher. However, the actual situation in China is the opposite. The markup of non-export firms is even higher. Therefore, scholars, who have observed this problem, have begun to use different markup-measurement methods to study this phenomenon, ranging from different angles, which include export tax rebates, import competition, and resource allocation. This paper reviews the literature from four aspects, which are the development of the variable markup trade theory, the development of markup measurement methods, the development of empirical research on China export firms’ abnormal markup phenomenon, and looks forward to the follow-up research, in order to make some contribution to continuously supplement and improve the research about this abnormal phenomenon in China.